SEMANTIC AND SYNTACTIC CHALLENGES IN TRANSLATING TECHNICAL NEOLOGISMS FROM ENGLISH TO UZBEK - Aripova Nasiba Rustamovna (Bright Mind Publishing, 2025)
The rapid evolution of technology and globalization has led to the proliferation of technical neologisms, posing significant challenges for translators working between English and Uzbek. These challenges are rooted in semantic and syntactic differences between the two languages, which belong to distinct language families. This article explores the difficulties encountered in translating technical neologisms, focusing on lexical, grammatical, and cultural aspects. It also examines strategies to overcome these challenges, ensuring accurate and culturally appropriate translations.
Keywords: Evolution, proliferation, technical neologism, cultural context.